Origin and evolution of solutional features on granitic inselbergs - Santos, Guilherme Lima Brasil dos; Maia, Rubson Pinheiro; Travassos, Luiz Eduardo Panisset; Souza, Anna Sabrina Vidal de (Revista Brasileira de Geomorfologia, 2023)
Inselbergs are landforms shaped by a number of erosion processes. They can be characterized either by a predominance of dissolution features or fracturing and occasionally exhibit massive slopes. In this study we demonstrate the main structural mechanisms driving the formation of dissolution features, such as gnammas. In granitic rocks, mafic ellipsoidal enclaves can act as a starting point for differential erosion. The enclaves and their orientation control the early stages of dissolution features (ellipsoidal microcavities and gnammas). In the Pedra do Cruzeiro inselberg, located in Quixadá, northeastern Brazil, 99 enclaves were analyzed in a 230m SW-NE transect on the inselberg slope. The data show that the primary trend of enclave orientation (86E on average) coincides with the orientation of the majority (97%) of dissolution features in their first and second stages. In advanced erosion phases in which mega karren are developed, they are not solely controlled by preexisting structural patterns, attesting to the superimposition of the surface runoff of the inselberg over the structure (e.g., magmatic foliation and mafic enclave orientation).